A Conceptual Review of Social Media Marketing Outcomes Brand Image and the Conditional Pathway to Purchase Intention - Deliana, Marlina; Poluan , Nadia Amelia Elyana; Simanjorang, Feronica (Talenta Publisher, 2026)
This study reviews prior research to explain how social media marketing (SMM) influences brand image, and ultimately purchase intention—and highlights that the link from SMM → purchase intention is often inconsistent and may depend on mediators. This is a conceptual / literature-based paper: it builds the framework using deductive reasoning and a systematic review of prior literature. The findings suggest that a strong brand image plays a crucial role in bridging the gap between social media marketing efforts and actual purchasing behavior.